2014
DOI: 10.1007/s00595-014-1091-1
|View full text |Cite
|
Sign up to set email alerts
|

Repeat hepatectomy with inferior vena cava re-resection for colorectal liver metastases: case report and review of the literature

Abstract: Liver resection in patients with inferior vena cava (IVC) involvement is becoming more common with the adoption of vascular exclusion techniques and replacement of the IVC. Repeat hepatectomy and an aggressive surgical approach can offer satisfactory disease-free survival and a cure in selected patients. We herein describe a case of repeat hepatectomy with en bloc re-do IVC resection and reconstruction with Gore-Tex graft for recurrent colorectal liver disease. The patient had previously undergone non-anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Presently, hepatectomy for CRLM is considered feasible once all metastatic diseases can be excised with anticipated negative surgical margins. Published series have documented favorable outcomes following hepatectomy with resection of EHD in a variety of settings [6-10]. While demonstrating feasibility, much of the current evidence is observational in nature based on small case series, making it difficult to interpret fairly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, hepatectomy for CRLM is considered feasible once all metastatic diseases can be excised with anticipated negative surgical margins. Published series have documented favorable outcomes following hepatectomy with resection of EHD in a variety of settings [6-10]. While demonstrating feasibility, much of the current evidence is observational in nature based on small case series, making it difficult to interpret fairly.…”
Section: Discussionmentioning
confidence: 99%
“…Extension of hepatic metastatic disease to involve adjacent viscera was traditionally a contraindication to resectability. However, with radiological advancements, multidisciplinary input and refinements in surgical technique, a number of studies have published favorable outcomes following resection of extrahepatic colorectal metastases [6-10]. In fact, where an R0 resection is achievable, combined hepatectomy and extrahepatic resection for CRLM has been associated with a comparable 5-year survival rate of 28%, to those undergoing CRLM resection in isolation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In one of the most comprehensive series including concomitant liver and vena cava resections, the mortality, morbidity, and 5-year survival rates were reported as 11%, 40%, and 37.7%, respectively [ 4 ]. A recent systematic review including 204 patients who had concomitant vena cava and liver resections for any reason demonstrated that the vena cava reconstruction after resection was made with a primary closure in 40% and in the 12% a patch was used for the defect [ 5 ]. In the remaining 98 cases, a circumferential vena cava resection was required and they were repaired by synthetic grafts but only in one case a homograft was used for caval replacement just like our case.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know there were only three reported cases that had a liver reresection and a concomitant vena cava resection [ 5 , 8 , 9 ]. The difficulties of the repeated liver resections were all mentioned in those reports and the risks were augmented with the vena cava resections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation